Channel flow and fault segmentation with implications for the generation of earthquakes in the Longmenshan fault zone, eastern Tibetan Plateau. (15th June 2019) - Fang, Peng; Hou, Guiting
Graphical abstract: The combined action of the channel flow and fault segmentation controls the distribution of stress and causes the generation of earthquakes in the Longmenshan fault zone. Highlights: The Longmenshan fault zone has a rheological structure and displays segmentation. The channel flow finger is closer to the segment II than segment I of the faults. Locking degree of segment II was higher than segment I before Wenchuan earthquake. Abstract: The Ms 8.0 Wenchuan earthquake occurred in the Longmenshan fault zone (LFZ) of the eastern margin of the Tibetan Plateau (TP). The tectonic activities in this region have been a focus of extensive studies in the past two decades. Two different models involving oblique stepwise rise and channel flow, respectively, are proposed and can be used to explain the generation of earthquakes. The oblique stepwise rise model emphasizes more about the fault of the upper crust, whereas the channel flow model concerns more about the different crustal rheological structures. Currently, because of the confirmation of geophysical data on the rheological structure of the TP, more researchers agree with the channel flow model. To investigate the generation of earthquakes in the LFZ, this study establishes a three-dimensional viscoelastic model based on the heterogeneity of the lithospheric structure and the segmentation of faults. Using ANSYS finite element software to simulate the evolution of stress and strain, the calculated results are consistent with focal mechanism solutions, fault striations, and topography. The best-fit stress field suggests that stress localization in the Longmenshan range is mainly controlled by the channel flow and fault segmentation. The differing viscosities and relative movement between the channel flow and the Sichuan Basin induce a concentration of stress in the LFZ. The stress was most concentrated in segment II, closest to the leading edge of the channel flow, and wherein the Wenchuan earthquake occurred. Additionally, the higher locking degree of segment II found before the Wenchuan earthquake induced higher stress levels at shallow depths, corresponding to higher seismic activity in segment II. Thus, the combined action of the channel flow and fault segmentation controls the distribution of stress and causes the generation of earthquakes in the LFZ.